Infiltrasi Peningkatan Peresapan Air ke Dalam Tanah Melalui Aplikasi Pupuk Organik Sekam Padi pada Pertanaman Sorgum (Sorghum bicolor, L.) - Nurmi .; Syamsul Bahri; Mohamad Arief Azis; Safrudin Dzakaria (Politeknik Negeri Lampung., 2023)
This study aimed to determine the effect of rice husk organic fertilizer on increasing the amount of infiltrated water and its correlation to sorghum yields. The use of organic rice husk fertilizer also minimizes rice husk waste. The research method used a randomized block design consisting of two factors, the variety and organic fertilizer factors. The variety factor consisted of 2 levels, namely the Numbu variety (V1) and the Kawali variety (V2), while the dose factor of organic fertilizer consisted of 3 levels, namely without the application of organic fertilizer (P0/control), 25 tons.ha-1 (P1) , and 50 tons.ha-1 (P2). Parameters observed at the end of the experiment included measuring soil physical properties, namely infiltration using a double ring infiltrometer, and measuring sorghum yields. Data analysis was performed by analysis of variance (ANOVA) with further tests using the Tukey test (5% BNJ). Correlation analysis was conducted to see the relationship between organic fertilizer dosage and seed weight per hectare with constant infiltration. Infiltration data from field measurements is processed to create an infiltration curve by modeling following the formula developed by Horton f = fc + (fo – fc) e-kt. The results of infiltration modeling based on the Horton model can be seen in the infiltration curve which shows that the P2 rice husk organic fertilizer produced the highest curve line compared to P1 and P0/control. The results of statistical analysis with the 5% BNJ test for constant infiltration showed that the P2 and P1 rice husk organic fertilizer treatments provided the same infiltration capacity, but the infiltration capacity values for the P2 and P1 rice husk organic fertilizer treatments were higher compared to P0/control. There is a very strong positive linear correlation between the dose of organic fertilizer and the weight of seeds per hectare with a constant infiltration value.